2023
DOI: 10.3390/brainsci13081173
|View full text |Cite
|
Sign up to set email alerts
|

Visual Dysfunction in Parkinson’s Disease

Abstract: Non-motor symptoms in Parkinson’s disease (PD) include ocular, visuoperceptive, and visuospatial impairments, which can occur as a result of the underlying neurodegenerative process. Ocular impairments can affect various aspects of vision and eye movement. Thus, patients can show dry eyes, blepharospasm, reduced blink rate, saccadic eye movement abnormalities, smooth pursuit deficits, and impaired voluntary and reflexive eye movements. Furthermore, visuoperceptive impairments affect the ability to perceive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 198 publications
0
9
0
Order By: Relevance
“…Dopamine significantly impacts several visual functions such as light adaptation, oculomotor function, contrast sensitivity, color perception, visuospatial construction, and spatial working memory. 12 Insufficient dopamine in PD leads to various visual abnormalities, including diplopia. PD patients are also prone to eyelid apraxia, blepharospasm, and dry eyes.…”
Section: Dopamine's Role In Visionmentioning
confidence: 99%
“…Dopamine significantly impacts several visual functions such as light adaptation, oculomotor function, contrast sensitivity, color perception, visuospatial construction, and spatial working memory. 12 Insufficient dopamine in PD leads to various visual abnormalities, including diplopia. PD patients are also prone to eyelid apraxia, blepharospasm, and dry eyes.…”
Section: Dopamine's Role In Visionmentioning
confidence: 99%
“…VIs have been widely used as a tool to investigate how visual perception develops (e.g., Doherty et al, 2010 ) and the impact of neuropsychological disorders such as schizophrenia (for a review see King et al, 2016 ; Costa et al, 2023 ) and autism (for a review see Gori et al, 2016 ). Although impairment of visual perception (e.g., hallucinations) is now well established in Parkinson’s disorder (PD) ( Sauerbier and Ray Chaudhuri, 2013 ; Weil et al, 2016 ; Nieto-Escamez et al, 2023 ), research has yet to investigate how PD affects susceptibility to VIs. Furthermore, depth perception—which is linked to VI susceptibility (e.g., Gregory, 1963 ; Doherty et al, 2010 ; Gregory, 2015 ) and increased risk of falling ( Cummings et al, 1995 )—is shown to be affected in PD ( Maschke et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine has also been shown to influence visual perception in PD. Multiple studies have found that retinal dopamine levels and dopaminergic innervation surrounding the fovea are reduced in PD ( Harnois and Di Paolo, 1990 ; Sauerbier and Ray Chaudhuri, 2013 ; Nieto-Escamez et al, 2023 ), resulting in visual perception deficits such as poorer light adaptation and decreased contrast sensitivity (e.g., Pieri et al, 2000 ; Armstrong, 2015 ). Other visual deficits that are linked to dopamine deficiency include greater thresholds for motion detection (e.g., Trick et al, 1994 ), color discrimination (e.g., Büttner et al, 1994 ), as well as visuospatial deficits (e.g., Gibson et al, 1987 ; for an overview of dopamine-related deficits in PD, see Brandies and Yehuda, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms include a range of visual issues, such as dry eyes, blink rate reduction, abnormal eye movements, contrast sensitivity and acuity problems, visuospatial challenges, attention difficulties, and perceptual disturbances, often leading to visual hallucinations. Nieto-Escámez et al's [25] review aims to provide a comprehensive understanding of these visual disruptions, exploring their neuroanatomical, functional, and neurochemical underpinnings, including the structural and functional changes in cortical and subcortical regions and their connections to neuropsychological findings, while also considering the involvement of various neurotransmitter systems like dopamine, acetylcholine, and serotonin.…”
mentioning
confidence: 99%